The regional impact of monetary policy on house prices. (1st January 2012) - Allen, Larry; Kenyon, George N.; Natarajan, Vivek S.
This paper examines how house prices respond to monetary policy in the nine census regions of the USA. A polynomial distributed lag regression model is estimated for each region. The dependent variable in each equation includes growth for the index of regional house prices. The independent variables include (1) growth for an index of national house prices, (2) difference between the regional unemployment rate and the national unemployment and (3) the growth in M2. The money stock variable enters each equation as a polynomial distributed lag. Given this specification, regional house prices are positively correlated with money stock growth in some regions, and negatively correlated in others.